HUBUNGAN PERAN KELUARGA DENGAN PELAYANAN PUSKESMAS PADA ANGGOTA KELUARGA YANG MENDERITA PENYAKIT KUSTA - ANWAR AMRULLAH (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: analyze differences in the effectiveness of breastfeeding and low-lactose milk formula to the duration of the healing of acute enteritis Gastro Methods: Cross Sectional research design was used, population in this researches all member of the family that has leprosy patient, and they were 40 people. Sample in this researches the leprosy ember is 36 people. Probability Sampling with Simple Random Sampling. The method is using questioner of Rank Spearman.  Results: The research got supported from the families as the respondent, they are 17 people (47.2%), community health center officer respondent are 23 (63.9%). The result iscorelasirank spearman get with P ; 0.002 and mistakes percentage  α: 0.05 (5%), until 0.002 <0.05 so there is relation between the patient family with the health worker in Puskesmas Arjasa Kecamatan Arjasa Kabupaten Sumenep with correlation coefficient 0.506 which mean strong. Conclusion: This reasearh is aiming to be reference to medic in improving the service. It is also hope that this reseaarh can be beneficial for families that taking care their member of family asa leprosy patient.